2015
DOI: 10.1080/15257770.2014.992532
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Thiopurine Pyranonucleosides: Evaluation of Their Bioactivity

Abstract: We report the synthesis of novel thiopurine pyranonucleosides. Direct coupling of silylated 6-mercaptopurine and 6-thioguanine with the appropriate pyranoses 1a-e via Vorbrüggen nucleosidation, gave the N-9 linked mercaptopurine 2a-e and thioguanine 4a-e nucleosides, while their N-7 substituted congeners 10a-e and 7a-e, were obtained through condensation of the same acetates with 6-chloro and 2-amino-6-chloropurines, followed by subsequent thionation. Nucleosides 3a-e, 5a-e, 8a-e, and 11a-e were evaluated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
3
4
0
Order By: Relevance
“…In the most promising report in the literature, peracetylated 6-chloro-7-(β-Dglucopyranosyl)purine (3a) was isolated in 60% yield by the modified Vorbruggen method. 50 However, we found that the NMR data they reported for the prepared compound corresponded to N 9 -isomer 4a and thus were consistent with the spectra of the N 9 -isomer in other reports where the NMR spectra of both isomers were provided. 18,30,33 Additionally, analogous N 7 -galactosyl 3d and mannosyl 3e derivatives were incorrectly described in this paper, which was verified experimentally in our work.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In the most promising report in the literature, peracetylated 6-chloro-7-(β-Dglucopyranosyl)purine (3a) was isolated in 60% yield by the modified Vorbruggen method. 50 However, we found that the NMR data they reported for the prepared compound corresponded to N 9 -isomer 4a and thus were consistent with the spectra of the N 9 -isomer in other reports where the NMR spectra of both isomers were provided. 18,30,33 Additionally, analogous N 7 -galactosyl 3d and mannosyl 3e derivatives were incorrectly described in this paper, which was verified experimentally in our work.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
“…An approximately equimolar ratio of N 7 /N 9 -isomers and a low conversion were observed several times during the reproduction of a similar procedure described in another publication (Table 1, entry 15). 50 Similar results in terms of isomer distribution were observed using SnCl 4 or TiCl 4 . An approximately equimolar ratio of both isomers was attained after 22 h at room temperature (Table 1, entries 16 and 19), and over time, the ratio changed to favor the N 9 -isomer 4a (Table 1, entries 17 and 20).…”
Section: ■ Results and Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…To date, three methods have been described. The most promising method, where peracetylated 6‐chloropurine‐7‐β‐ d ‐glucopyranoside was isolated in 60% yield, was reported in a literature . We repeated this procedure with unlabeled 1 and found that authors prepared 9‐isomer 2 instead of 7‐isomer 3 .…”
Section: Resultsmentioning
confidence: 99%